Real-world safety assessment of Ixekizumab based on the FDA Adverse Event Reporting System (FAERS) - Yuzhe Cheng; Jingyi Ma; Jun Niu (PLoS ONE, 2025)
Background Ixekizumab, a monoclonal antibody targeting IL-17A, is approved for psoriasis (PsO) and psoriatic arthritis (PsA). While clinical trials demonstrate its efficacy, real-world safety insights remain critical due to limitations in detecting rare or delayed adverse events (AEs). Methods This study analyzed 28,889 ixekizumab-associated AE reports from the first quarter of 2016 to the third quarter of 2024 in the FDA Adverse Event Reporting System (FAERS) using disproportionality methods (ROR, PRR, MGPS, BCPNN) and Weibull distribution modeling. Subgroup and sensitivity analyses were conducted to evaluate demographic variations and confounding factors. Results Common AEs included injection site reaction, fungal infections, and upper respiratory infections. Novel signals included myocardial infarction, herpes zoster, and inflammatory bowel disease. Subgroup analyses revealed male-predominant cardiac risks and age-dependent patterns (pediatric injection reactions vs elderly herpes zoster). Median time-to-onset was 56 days (IQR:12–205), with early risk escalation (Weibull β = 0.60). Conclusions This FAERS analysis confirms ixekizumab’s established safety profile while identifying critical demographic-specific and delayed-onset signals. Continuous pharmacovigilance is warranted to optimize risk management, particularly for cardiovascular monitoring in high-risk males and antiviral prophylaxis in elderly patients.